Enhancement of hydrodesulfurization of 4, 6-dimethyldibenzothiophene catalyzed by CoMo catalysts supported on carbon-covered γ-Al2O3. Issue 1 (6th October 2014) - Cui, Feng; Li, Guangci; Li, Xuebing; Lu, Mohong; Li, Mingshi
Abstract : Carbon species deposited on supports can shorten MoS2 slab length and increase the number of easily reducible sulfur species relative to HDS activity. Abstract : The carbon-covered aluminas were prepared by using different monocarboxylic acids as carbon sources to modify active alumina, and then were used as supports to prepare supported CoMo catalysts for hydrodesulfurization (HDS) of 4, 6-dimethyldibenzothiophene (4, 6-DMDBT). These monocarboxylic acid molecules can be readily converted to carbon species by thermal decomposition in a nitrogen atmosphere and deposited on an alumina surface. The carbon species can then effectively weaken the interaction between active metals and alumina, which improves the migration and growth of surface Mo species. This result further affected the morphology and orientation of surface sulfur species, that is, the slab length and stacking number of the MoS2 slabs, which closely relates to HDS activity. Since the surface Mo species supported on the alumina modified with acetic acid consisted of the MoS2 slabs with the shortest lengths, leading to the presence of more easily reducible sulfur species during the reaction, the corresponding catalyst exhibited the highest HDS activity for 4, 6-DMDBT. In addition, the stacking numbers for all of the catalysts were relatively low, which hindered the adsorption of 4, 6-DMDBT on the brim sites of the MoS2 stacks, and thus the HDS reaction mainly occurred through the direct desulfurization route.